Mechanism for Handling of Criminal Action Prohibiting the Use of Land Without Permission - Dwi Anas Rudiyantoro; Sri Kusriyah (Universitas Islam Sultan Agung, 2021)
The aim of this research is; to find out and analyze the mechanism for handling criminal cases prohibiting the use of land without a permit. Toknow and analyze obstacles in handling criminal cases prohibiting the use of land without a permit. To know and analyze solution to overcome the problem of handling criminal cases prohibiting the use of land without a permit. This study uses a sociological juridical approach, with descriptive analytical research specifications. The results of this study are the mechanism for handling criminal cases prohibiting the use of land without a permit contains the procedures and procedures for handling, terminating and settling Police Reports up to the District Court level. Constraints, namely: a) Limited police investigator personnel. b) Lack of facilities and facilities. c) Lack of police expertise in handling criminal cases of land grabbing. d) Difficulty in calling witnesses. e) Difficulty finding expert information. f) The old reporting party reports to the police after the crime has occurred. The solution is a) Adding personnel to the investigation team at the Cirebon City Police Reskrim Unit I. b) Conducting a coordination relationship between the Cirebon City Police and the Cirebon City National Land Agency. c) Conduct a search for heirs and visit the witness's domicile.